Assessment of Peat Extraction Range and Vegetation Succession on the Baligówka Degraded Peat Bog (Central Europe) Using the ALS Data and Orthophotomap - Jucha, Witold; Mareczka, Paulina; Okupny, Daniel (Remote sensing (Basel, Switzerland), 2022)
The Baligówka peat bog is one of the peat bogs of the Orawa-Nowy Targ Basin—the largest complex of wetlands in the Polish Carpathians. Its area has declined in the past as a result of drainage and peat exploitation, which caused a bad hydrological condition and it is gradually overgrown by non-peat bog medium and high vegetation. The research uses models derived from airborne laser scanning (ALS) and an orthophotomap to delimit the bog and divide it into parts and assess the range of drainage ditches and vegetation. The area of the peat dome along with 3 sites of peat exploitation is currently 159.6 ha, while the ecotone zone is 105.9 ha. Both sections are separated by a steep post-mining slope. The medium and high vegetation areas cover 44% of the peat bog; its location is related to the dense drainage system in the southern part of the dome. The parameters of the Baligówka peat bog: area, size and extent of drainage system, and the degree of overgrowth by high vegetation, are the subject of research towards the protection under the Natura 2000 network (PLH120016) and the establishment of a plan for restoration activities.